Microvessel density as a prognostic factor in esophageal squamous cell cancer patients: A meta-analysis. Issue 29 (July 2017) - Ma, Guangzhi; Zhang, Jing; Jiang, Hai; Zhang, Nannan; Zhu, Yunjie; Deng, Yunfu; Zhou, Qinghua
Abstract: Background: To date, literature has emerged that shows contradictory results about the prognostic role of microvessel density (MVD) in esophageal squamous cell cancer (ESCC). The aim of the study set out to evaluate the correlation between MVD and the prognosis of ESCC. Methods: Identified publications from various databases were obtained and reviewed. A meta-analysis was performed to evaluate the prognostic role of MVD among ESCC patients. Results: A total of 11 eligible studies containing 891 ESCC cases were included in the meta-analysis. The pooled hazard ratio for overall survival was 2.39 (95% confidence interval 1.92–2.96, P < .001). Heterogeneity among the studies was not significant, and publication bias was not found. Subgroup analyses were also performed on different issues, such as districts, antibodies, and median age. Conclusion: High MVD is a prognostic factor among ESCC that indicated worse prognosis in these patients. More studies are needed, and through abundant evidence, the topic could be re-evaluated by then.